Splicing variant of WDFY4 augments MDA5 signalling and the risk of clinically amyopathic dermatomyositis. Issue 4 (13th January 2018) - Kochi, Yuta; Kamatani, Yoichiro; Kondo, Yuya; Suzuki, Akari; Kawakami, Eiryo; Hiwa, Ryosuke; Momozawa, Yukihide; Fujimoto, Manabu; Jinnin, Masatoshi; Tanaka, Yoshiya; Kanda, Takashi; Cooper, Robert G; et al.
Abstract : Objectives: Idiopathic inflammatory myopathies (IIMs) are a heterogeneous group of rare autoimmune diseases in which both genetic and environmental factors play important roles. To identify genetic factors of IIM including polymyositis, dermatomyositis (DM) and clinically amyopathic DM (CADM), we performed the first genome-wide association study for IIM in an Asian population. Methods: We genotyped and tested 496 819 single nucleotide polymorphism for association using 576 patients with IIM and 6270 control subjects. We also examined the causal mechanism of disease-associated variants by in silico analyses using publicly available data sets as well as by in in vitro analyses using reporter assays and apoptosis assays. Results: We identified a variant in WDFY4 that was significantly associated with CADM (rs7919656; OR=3.87; P=1.5×10 −8 ). This variant had a cis-splicing quantitative trait locus (QTL) effect for a truncated WDFY4 isoform (tr- WDFY4 ), with higher expression in the risk allele. Transexpression QTL analysis of this variant showed a positive correlation with the expression of NF-κB associated genes. Furthermore, we demonstrated that both WDFY4 and tr-WDFY4 interacted with pattern recognition receptors such as TLR3, TLR4, TLR9 and MDA5 and augmented the NF-κB activation by these receptors. WDFY4 isoforms also enhanced MDA5-induced apoptosis to a greater extent in the tr-WDFY4-transfected cells. Conclusions: As CADM is characterised by the appearance of anti-MDA5 autoantibodies and severe lung inflammation, the WDFY4 variant may play a critical role in the pathogenesis of CADM.